INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY, PRICE AND PACKAGING ON CONSUMER LOYALTY IN BEAR BRAND MILK (Case Study of Tebing Tinggi Supermarket Irian Consumers) - CANDRASA, LIMEGA (Universitas Efarina, 2022)
This study aims to determine the effect of brand image, product quality, price and packaging significantly and simultaneously on consumer loyalty. The sample determination method used in this study uses a non-probability sampling technique of 98 samples who are consumers of Irian Supermarket Tebing Tinggi. Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is rejected, meaning that the price variable (X3) has no significant effect on the consumer loyalty variable (Y). Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Brand Image variable (X1) has a significant effect on the Consumer Loyalty variable (Y). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is accepted, meaning that the Product Quality variable (X2) has a significant effect on the Consumer Loyalty variable (Y). Based on the results of the analysis of hypothesis 4, it can be concluded that the fourth hypothesis is accepted, meaning that the packaging variable (X4) has a significant effect on the consumer loyalty variable (Y). Based on the results of the analysis of hypothesis 5, it can be concluded that the fifth hypothesis is accepted, meaning that the variables Brand Image (X1), Product Quality (X2), Price (X3) and Packaging (X4) simultaneously influence the Consumer Loyalty variable (Y). meaning that the packaging variable (X4) has a significant effect on the consumer loyalty variable (Y). Based on the results of the analysis of hypothesis 5, it can be concluded that the fifth hypothesis is accepted, meaning that the variables Brand Image (X1), Product Quality (X2), Price (X3) and Packaging (X4) simultaneously influence the Consumer Loyalty variable (Y). meaning that the packaging variable (X4) has a significant effect on the consumer loyalty variable (Y). Based on the results of the analysis of hypothesis 5, it can be concluded that the fifth hypothesis is accepted, meaning that the variables Brand Image (X1), Product Quality (X2), Price (X3) and Packaging (X4) simultaneously influence the Consumer Loyalty variable (Y).